From nature to nano: Biomass-derived MXenes as a precursor for multifunctional energy and biomedical materials - Muzammal, Sadia; Tariq, Sadaf; Muhamad, Mat Noor; Ditta, Fozia Allah; Ahmad, Awais; Ali, Shafaqat; Khalid, Hafsa; Shahzad, Muhammad (Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim, 2025)
MXenes are exfoliated flakes of two-dimensional (2D) inorganic materials, comprising of ultrathin atomic thickness of multilayered transition metal nitrides, carbides, or carbo-nitrides with the general structural formula M n+1 X n T x (n=1–3), derived from their parent MAX phase etching out of “A”. They are known for their excellent conductance, hydrophilicity, biocompatibility, tunability, and active surface termination properties. The tailored materials have surface terminators, especially hydroxyl, oxide, or fluoride groups, which impart hydrophilicity and make their surfaces active. The highly controlled surface terminators, presence of solid solutions, and recent advances of multiple transition metals layered MXenes offer new areas and potential for rational design and synthesis of various novel structures. This review provides an exclusive and detailed overview of underlying techniques to prepare multilayered biomaterial-based MXenes and elaborates on the innovations in synthesis techniques to gain key insights into biomaterial/MXene composites. Briefly, the unique performance correlated to biomaterial/MXene composites with their characteristic properties is also mentioned. Last, future research commands for large-scale synthesis and stabilisation policies, along with the previously presented synthesis routes of biomaterial/MXene composites, are proposed to encourage advances in the field of 2D MXenes and develop their boundaries for various stoichiometric compositions as well as applications.